ANALISIS STATUS MUTU AIR SUNGAI BANJAR DESA BANJAR BARA KECAMATAN GAPURA KABUPATEN SUMENEP MENGGUNAKAN METODE STORET - Rodu Dhuha Afrianisa; Tsanialtul Ulyah (Jurnal Sains & Teknologi Lingkungan, 2023)
Banjar river in West Banjar Village, Gapura District, Sumenep Regency, is used by the local community for bathing, washing and toilet activities. This activity was carried out directly into the river, causing river water pollution. In addition to the bathing and washing activities in the river, there was tofu wastewater deliberately dumped directly into the Banjar River. Pollution load increased in river. Under these conditions, research is needed to determine the amount of pollution in the Banjar River and determine the status of water quality to describe the level of water pollution. Quantitative descriptive method is the approach used in this test using the paraThe quantitativ OD,BOD, COD, pH, TSS. Water quality standarts is guided by PP RI Number 22 of 2021 while the regulations for determining water quality status using the storet method are guided by KepMen LH No.115 of 2003. The Banjar River is divided into 4 segments based on pollutant sources and the characteristics of the Banjar river. Segment determination characteristics include kilometers from downstream, length and geographic coordinates. All water quality parameters were analyzed for ,trends in concentration changes and correlations between parameters. The test results show that based on the COD, TSS and pH parameters in the Banjar river meet the quality standards while the ,DO and BOD parameters for each sampling point produce values ​​that exceed the quality standards. Water quality status based on the storet method at points A, B, D, and E scores between -8 until -10 with the status of "Slightly Polluted" while point C has a value of -12 with the status of "Moderately Polluted".